Antioksidativni potencijal ekstrakta kore nara: in vitro i in vivo studije - Mandić-Kovačević, Nebojša; Kukrić, Zoran; Latinović, Staniša; Cvjetković, Tanja; Šobot, Tanja; Bajić, Zorislava; Maličević, Uglješa; Marinković, Sonja; Đukanović, Đorđe; Uletilović, Snežana; Suručić, Relja (Scripta Medica, 2023)
Background/Aim: Due to the numerous beneficial effects of pomegranate that can be explained through its antioxidative effects, the aim of this study was to determine the antioxidant potential of pomegranate peel extract (PoPEx) prepared from pomegranate that was harvested in the south-east region of Herzegovina (Bosnia and Herzegovina), through in vitro and in vivo studies.Methods: The total phenols, flavonoids, flavonols, flavan-3-ols and anthocyanins content was determined, as well as several antioxidative assays, including 2,2 diphenyl-1-picrylhydrazyl assay (DPPH), 2,2'-azino bis(3-ethylbenzothiazoline-6-sulfonic acid)  assay (ABTS), iron (III) - 2,4,6-tripyridyl-S-triazine complex assay (FRAP), reduction of copper(II) ions (CUPRAC) assay, Briggs-Rauscher oscillatory reactions, neutralization of OH radicals and lipid peroxidation assay. In vivo studies were performed by administrating 100 mg/kg of body weight of PoPEx to the rats by gavage for 7 days, after which the rats were euthanised and prooxidative parameters (thiobabrituric acid reactive substances - TBARS  as an index of lipid peroxidation, nitrites - NO2, hydrogen peroxide - H2O2 and superoxide anion radical O2-) were determined in plasma, as well as antioxidative parameters (superoxide dismutase - SOD, reduced glutathione - GSH and catalase - CAT) in erythrocyte lysates.Results: High content of phenolic compounds was found in PoPEx, which resulted in high antioxidative potential in all in vitro tests performed. In vivo study showed that PoPEx administration caused a significant decrease in TBARS, NO2-, as well as an increase in reduced glutathione (p
Keywords: Ekstrakt kore nara; Antioksidativni kapacitet; Fenolna jedinjenja